What's New in Pediatric Orthopaedic Tumor Surgery. Issue 2 (February 2021) - Williams, Amy K.; Crawford, Brooke; Federman, Noah C.; Bernthal, Nicholas; Arkader, Alexandre
Abstract : Background: Pediatric Orthopaedic Oncology is a developing subspecialty within the field of Pediatric Orthopaedics. Traditionally, the field of Orthopaedic Oncology has been focused on the skeletally mature individual, and the research tends to be all encompassing rather than truly evaluating isolated populations. The purpose of this review is to summarize the most clinically relevant literature in the field of Pediatric Orthopaedic Oncology over the last 6 years. Methods: We evaluated the PubMed database utilizing keywords for pediatric orthopaedic oncology: sarcoma, osteosarcoma, Ewing sarcoma, bone cyst. In additionally, we further broadened our search by searching for relevant articles in the contents sections of major orthopaedic surgery journals that routinely publish both pediatric and orthopaedic oncology literature. In keeping with "What's New, " we selected the most clinically relevant articles published in the last 6 years from January 1, 2014 through February 2020. Basic science and systemic therapies literature was widely reviewed and the research and clinical trials most relevant to pediatric sarcoma and neoplastic processes found in the pediatric population were included. Results: Our search yielded 60 articles that met general criteria, from which 14 were determined to be most relevant to the goals of this paper. Of the papers presented in this review, there were papers related to management of benign tumors/tumor-like conditions, bone cysts, limb salvage procedures, and amputation procedures. Ultimately included in the review were 5 studies related to limb salvage, 4 related to bone cysts, 1 related to multiple hereditary exostoses, 2 related to osteofibrous dysplasia, 1 related to chondroblastoma, and 1 discussing cementation in skeletally immature patients. They were level III, IV, and V studies. Basic science and systemic therapies literature was widely reviewed and the research and clinical trials most relevant to pediatric sarcoma and neoplastic processes found in the pediatric population were included. Our search of the basic science and systemic therapies literature yielded 19 sources were found to be pertinent to our aims and 18 of those sources were published between 2015 and 2020. Conclusions: There are many, varied, and creative procedures in the realm of limb salvage, though there remains a lack of high-level evidence to support some of the more novel procedures. In regards to benign bone tumors, despite a more solid base of literature, there still does not seem to be consensus as to the best treatment. In particular, there continue to be many schools of thought on the treatment of benign bone cysts. Research in the basic science arena and systemic therapies are advancing in exciting ways in regards to pediatric sarcoma. Orthopaedic oncologic research specific to the pediatric population overall continues to be impeded by low sample sizes and inadequate levels of evidence, which limits the ability of surgeons to draw definitive conclusions from the literature.